PENDIDIKAN ISLAM BERBASIS KECERDASAN MAJEMUK - Ahmad Zain Sarnoto; ahmad Fathoni (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2020)
Many Islamic educational institutions loss of orientation, between following term of present educational model and surviving as it is. This phenomenon causes many Islamic educational institutions tend to bandwagon even willing to forget the Islamic identity as the basis of excellence. Improved quality by finding the right strategy to again raise excellence is a necessity, which is the theory of multiple intelligences initiated by Prof. Howard Gardner, who looked at that all the students are smart and unique, in line with the view to appreciate all the fitrah of creation without focusing to find student disabilities. This opinion against the old opinion about Intelligence Quotients (IQ) theory initiated by Alfred Binet in France, which is still used in Indonesian schools to reject students 'dumb' as the embodiment of the best school term